Research perspectives and further studies on catalyst effects on the stability of different polyethylenes during multiple extrusion: Inter‐relationship of oxidation chemistry and antioxidant activity. Issue 2 (19th May 2021) - Allen, Norman S.; Liauw, Christopher M.; Edge, Michele; Hoang, Eric; Fontan, Eusebio
Abstract: The degradation and stabilization of an extensive range of unstabilized and stabilized polyethylenes during multiple extrusions are examined in order to investigate and determine their chemical and structural changes and inter‐relationship with different commercial antioxidant/stabilizer packages including nondust blends. Unsaturation changes were also assessed after each extrusion. Oxidative stability was also evaluated by hydroperoxide analysis and carbonyl index. Metal catalysts residues of the neat polymers were determined and their contribution toward the overall oxidative stability of the polymers assessed along with the activity of the phenolic/phosphite antioxidants (as determined by HPLC). All the chromium‐based HD polyethylenes and the metallocene LLDPE crosslinked during multiple extrusions. The HDPE with high Cr/Ti and Al levels underwent chain scission after the second extrusion. The results indicated that crosslinking reactions during processing were initiated at the unsaturated groups. Melt flow index (MFI) changes observed during processing were accompanied by vinyl disappearance and trans ‐vinylene formation. The addition of alkyl radicals to vinyl unsaturations appears to be the main reaction. All stabilized packages effectively inhibited carbonyl growth during multiple extrusions but did not inhibit MFI change due to the crosslinking reactions, except for one LLDPE. Abstract : Catalytic decomposition of hydroperoxides by metallic compounds POOH + M n + ➔ PO . + M n + 1 + + OH − POOH + M n + 1 + ➔ POO . + M n + + H + 2POOH + M + / M n + 1 + ➔ PO . + POO . + H 2 O MFI decline during multiple extrusions of stabilized PE catalyzed by metal ions. All the chromium‐based HD polyethylenes and the metallocene LLDPE crosslinked during multiple extrusions. The HDPE with high Cr/Ti and Al levels underwent chain scission after the second extrusion.